EXAMINING THE EFFECTS OF SOCIAL MEDIA MARKETING, WORD OF MOUTH, AND STORE ATMOSPHERE ON CONSUMER PURCHASE BEHAVIOR: A CASE OF PAPERMINT COFFEE - I Gusti Ngurah Agung Hardi Mahardika; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
Product superiority can influence purchasing decisions for that product. This study aims to determine the influence of social media marketing, word of mouth, and store atmosphere on purchasing decisions. The research method used was quantitative. The population used was Papermint Coffee consumers and the sample consisted of 102 people. Data analysis techniques used were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Determination Coefficient, F Test, and t Test. The results of the study show that social media marketing has a positive and significant effect on purchasing decisions, word of mouth has a positive and significant effect on purchasing decisions, and store atmosphere has a positive and significant effect on purchasing decisions. The researcher's suggestion is that Papermint Coffee should recruit employees who are specifically tasked with managing social media so that they can respond quickly to any questions asked through social media, always offer products that consumers need so that consumers are willing to recommend them to others, arrange tables and chairs that are not yet properly arranged, and always offer products that are superior to those of competitors.